Defesas direta e indireta contra Tetranychus urticae Koch, 1836 (Acari: Tetranychidae) em tomateiros tratados com indutores - Silveira, Érika Carla da (2017)
The jasmonic acid (JA) and salicylic acid (SA) play an important role in the regulation of plant defense responses against herbivorous attack. It has been shown that JA and SA are effective in potentiating the induced defensive responses of plants. They increase the expression of genes related to the production of toxic compounds and the emission of volatile organic compounds attractive to the natural enemies of herbivores. In the present study, it was investigated the host preference and the performance of Tetranychus urticae Koch (Acari: Tetranychidae) on tomato plants (Solanum lycopersicum L., Solanaceae) infested by cospecific herbivores and/or Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) and also, the induction of direct and indirect resistance to T. urticae, via exogenous application of methyl jasmonate (MeJA) and / or methyl salicylate (MeSA) in tomato. In test with chance of choice, the T. urticae females preferred to oviposit in plants infested by T. absoluta in relation to noninfested or infested plants with co-specific. In test with no chance of choice, the females deposited a larger number of eggs in plants infested by T. absoluta as well as by the coespecific ones in compare with as non-infested plants. However, the spider mite had a superior performance, measured in terms of the number of immature, only in plants infested by the co-specifics. In olfactometry tests, the olfactory behavior of the mite did not explain the host preference for oviposition, since females did not discriminate the volatiles of plants in the different treatments. As for the application of the inducers, behavioral tests in a greenhouse showed that the number of eggs and adults of the spider mite was smaller in plants treated with MeJA and MeJA/MeSA in comparison to the control (Tween). Regarding the immature of the spider mite, the numbers were lower in treated plants with the inductor when compared to control. In relation to the indirect defenses, measured in terms of predator mite Phytoseiulus macropilis (Banks) (Acari: Phytoseiidae) attraction, the predator females were recaptured in a greater number in plants treated with MeSA in comparison to the other treatments. The predator females also deposited a larger number of eggs in plants treated with MeSA in relation to those treated with MeJA/MeSA. The application of the inducers reduced the concentration of total phenols in treated tomato plants when compared to control in the first collect, in spite of this, in the second collect there was a reduction only in plants treated with MeJA. About the lignin, in the first collect there was a reduction in plants treated with the inductors in relation to Tween, however, in the second collect there was not any difference between treatments. Thereby, this study has shown that a host selection by T. Urticae for oviposition it is not associated with improved offspring performance, and, also showed that infestation of T. Urticae induces susceptibility to the co-specifics. As well, the results suggest that non- volatile chemical tracks are responsible for host selection of T. urticae for tomato plants infested with co- specifics and/or T. absoluta. The results also indicates that MeJA promoted direct resistance of the tomato plant against T. urticae while the indirect resistence was induced only by the isolated application of MeSA.